Educational software and improvement of first grade school students’ knowledge about prevention of overweight and obesity - Santos Vital Alves Coelho, Luana; Vilanova Novais, Felipe Roner; Armaneli Macedo, Giulia; Nunes Neves dos Santos, Júlia; Lara Sousa, Vinícius; Mattos Mendes, Luis Augusto; Morais dos Reis, Daniel; Caetano Romano, Márcia Christina (Investigación y Educación en Enfermería, 2016)
Objective. To evaluate the effects of educational software to improve first grade school students’ knowledge about prevention of overweight and obesity. Methods. This non-controlled trial with a before-and-after evaluation was carried out in an school located in the municipality of Divinópolis (Brazil) among 71 students aged 6 to 10 years. The educational software about prevention of overweight and obesity was designed and then validated. The educational intervention comprised the use of the software. Before and after of the intervention we applied a questionnaire based on the Ten Steps to Healthy Eating for Children, proposed by the Brazilian Ministry of Health. Results. Comparing the times before and after application of the educational software, we observed statistically significant differences in proportion of questions answered correctly by first grade school students, mainly concerning daily eating of healthy and unhealthy food, adequate preparation of food and importance of exercise. Conclusion. This study highlights the importance of educational actions using software to build knowledge of first grade school students about prevention of overweight and obesity. How to cite this article: Coelho LSVA, Novais FRV, Macedo GA, Santos JNN, Sousa VL, Mendes LAM, Reis, DM, Romano MCC. Educational software and improvement of first grade school students’ knowledge about prevention of overweight and obesity. Invest. Educ. Enferm. 2016; 34(2):